Investigating the domestic cat's apparent predisposition to chronic kidney disease and hyperthyroidism - Alborough, Rebecca (2021)
Chronic kidney disease (CKD) and hyperthyroidism are two age-related diseases that are especially prevalent in domestic cats, compared to other species. This thesis explored potential reasons for the relatively high prevalence of these diseases in domestic cats. In particular, consumption of high levels of fish by domestic cats, relative to other companion animal species, such as dogs, and their wildcat ancestors, was considered. Study 1 investigated whether pro-oxidant minerals, such as arsenic and mercury, that are abundant in fish and which may instigate or progress CKD via oxidative stress mechanisms, may accumulate in domestic cat kidneys and associate with the presence of chronic interstitial nephritis (CIN). Although domestic cats, compared to dogs and Scottish wildcats, have greater arsenic concentrations in their kidneys and urine, suggesting increased arsenic consumption, the predominant arsenic species in fish-containing cat foods with high total arsenic content is arsenobetaine and therefore, presents low risk of renal toxicity. Arsenic concentration did not associate with the presence of CIN and mercury and iron concentrations were lower in cat kidneys, than in dogs. Domestic cat kidneys appeared to have depleted protective and/or antioxidant trace elements, including copper, zinc, rubidium and strontium, relative to dog kidneys, which may contribute to the increased prevalence of CIN in aged domestic cats’ kidneys.